Mint The Genus Mentha - Lawrence, Brian M;Ed (Medicinal and aromatic plants--industrial profiles, v. 44., 2007)
Presents an in-depth look at the genus Mentha, providing information on its history, production, chemical constituents, market trends, and medicinal and nutritional uses. This book covers the complex aspects of the cultivation, processing, and quality assessment of the different types of mint.